To solve the quadratic equation \(x^2 - 6x - 16 = 0\) using the quadratic formula, we start by identifying the coefficients:
- \(a = 1\)
- \(b = -6\)
- \(c = -16\)
The quadratic formula is given by:
\[ x = \frac{-b \pm \sqrt{b^2 - 4ac}}{2a} \]
First, we calculate the discriminant (\(b^2 - 4ac\)):
\[ b^2 = (-6)^2 = 36 \] \[ 4ac = 4 \cdot 1 \cdot (-16) = -64 \]
Now, compute the discriminant:
\[ b^2 - 4ac = 36 - (-64) = 36 + 64 = 100 \]
Now we can substitute back into the quadratic formula:
\[ x = \frac{-(-6) \pm \sqrt{100}}{2 \cdot 1} \] \[ x = \frac{6 \pm 10}{2} \]
Now, we solve for the two possible values of \(x\):
- For \(6 + 10\):
\[ x = \frac{16}{2} = 8 \]
- For \(6 - 10\):
\[ x = \frac{-4}{2} = -2 \]
Thus, the solutions to the equation \(x^2 - 6x - 16 = 0\) are:
\[ x = 8 \quad \text{and} \quad x = -2 \]
Among the given responses, the correct one is:
x=8, x=−2 (or x equals 8, x equals negative 2)